The last delivery - Dahm, Evan (Iron Circus Comics, 2024)
A parcel delivery boy arrives at a sprawling, chaotic mansion, in search of The Resident, who must sign for the package he bears, but this isn't nearly as simple a task as it should be.--Publisher.